2017
DOI: 10.1016/j.jnucmat.2017.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scale chemical evolution in a proton-and neutron-irradiated Zr alloy

Abstract: A. Harte et al., Nano-scale chemical evolution in a proton-and neutron-irradiated Zr alloy J. Nucl. Mater. Accepted Jan. 2017 Nano-scale chemical evolution in a proton-and neutron-irradiated Zr alloy (Fe,Ni). This is accomplished through ultra-high spatial resolution scanning transmission electron microscopy and the use of energy-dispersive X-ray spectroscopic methods. Fe-depletion is observed from both SPP types after irradiation with both irradiative species, but is heterogeneous in the case of Zr(Fe,Cr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…This irradiation-induced precipitation may provide barriers to dislocation loop glide and therefore increase the stability of the dislocation structure compared to alloys that show little irradiation-induced precipitation. This phenomenon may explain the lower temperature required for annealing in the Zr-0.1Fe sample studied here, where we do not have such precipitates away from the sparsely distributed SPPs, compared to neutron-irradiated Zircaloy-2 where irradiation-induced clustering has been observed throughout the matrix [20,21,49]. A particular benefit of this approach is that any sample-to-sample variation is eliminated during such in-situ analysis, compared to ex-situ studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This irradiation-induced precipitation may provide barriers to dislocation loop glide and therefore increase the stability of the dislocation structure compared to alloys that show little irradiation-induced precipitation. This phenomenon may explain the lower temperature required for annealing in the Zr-0.1Fe sample studied here, where we do not have such precipitates away from the sparsely distributed SPPs, compared to neutron-irradiated Zircaloy-2 where irradiation-induced clustering has been observed throughout the matrix [20,21,49]. A particular benefit of this approach is that any sample-to-sample variation is eliminated during such in-situ analysis, compared to ex-situ studies.…”
Section: Discussionmentioning
confidence: 92%
“…Specially fabricated Zr-Fe binary alloys have been used in this study to eliminate some of the complexity inherent in commercial alloy systems, whilst retaining key aspects of material evolution under irradiation, allowing the effect of specific microstructural features to be evaluated. Proton irradiation has previously been shown to be a good surrogate for neutron-irradiation in Zr alloys, providing similar damage structures and chemical evolution [10,[20][21][22][23]. Proton irradiation allows for the design of systematic studies, achieving comparable damage levels in short timescales with low residual activity compared to neutron-irradiated samples.…”
Section: Introductionmentioning
confidence: 99%
“…Further, because the test matrix is so large in these studies, the compositions reported are a single measurement for an alloy/heat treatment condition; no indication is given in regards to compositional variation or error in the measurement itself. Although it is important to obtain data from a large number of particles for good statistics to assess phase compositional range (see the work of Harte et al in [67] for the compositional range of precipitates in Zircaloy-2 as a function of proton and neutron irradiation dose), it is more important to perform accurate and precise measurements through good practise; doing so will allow proper comparisons between different studies and reliable conclusions. Regardless of the lack of any compositional range in these reports, the volume fraction of reported Zr(Nb,Fe)2 relative to (Zr,Nb)2Fe has been shown as dependent on alloy composition [64] and the importance of long annealing times to reach equilibrium phase compositions has been demonstrated, especially at low annealing temperatures [3,22], e.g.…”
Section: The Hexagonal Zr(nbfe)2 and Cubicmentioning
confidence: 99%
“…The second regime is at normal operating irradiation temperatures and results in Fe loss and coupled amorphisation progressing from the particle periphery inwards with increasing irradiation dose [72,73,75,76], this process being quicker at the lower end of the operating temperature range at 270 °C [77]. The final regime is at high neutron or proton irradiation temperatures and results in Fe loss without amorphisation, re-precipitation in the matrix and even particle growth [53,67,75,78]. Whilst these temperature regimes may show resemblance to the three modes of evolution in the hexagonal ZrNbFe phase, it is important to note that, for the Zr-Nb-Fe alloys, the particle(s) that display progressive amorphisation and those that display transformation from HCP to BCC were irradiated in the same temperature and dose rate regime, yet they were reported to be the same phase initially.…”
Section: The Hexagonal Phasementioning
confidence: 99%
“…The study of the amorphisation transformation of these SPPs has not been conducted as part of this work, as the main aim is to address the effect of the redistributed Fe. A detailed study of the SPPs, and the segregation of the other major alloying elements in the proton-irradiated Zircaloy-2 samples, can be found elsewhere [43].…”
Section: Nature Of Tilted Defectsmentioning
confidence: 99%